A Practical Mentorship Model for Raising Learning Outcomes among Academically Low Achieving Students in Machakos University - Muola, James M.; Mulwa, David; Kimiti, Peter; Amukowa, Wycliffe (European Journal of Education Studies, 2019)
Academic mentorship has been practiced in a number of universities including Machakos in Kenya though ineffectively due to the large student numbers and the presumably misconceived assumption that all students are in need and will voluntarily seek assistance. Most of the students admitted in public universities have the potential to excel academically if properly guided, supported and challenged. For academic mentorship to be successful and profitable to students, there is need to come with a workable model suitable for Kenyan universities. The main objectives of this study were to improve learning outcomes of academically low achieving students through mentorship, test an academic mentorship model for Machakos University, enhance mentorship competences of academic staff in Machakos University, and to develop mentorship resources for use by academic staff and students of Machakos University. The study used the time series experimental design in which 239 academically low achieving students were purposively selected on the basis of their performance. The selected students had failed between one and four units during the January-April 2018 semester. Each mentor was allocated ten students and advised to meet with them for at least five times during the semester. The mentees were subjected to a rigorous academic mentorship process for one semester and their end of semester performance was compared with the performance in the preceding semester. The study mainly used documentary analysis to gather the required data. Data was analysed using descriptive statistics. Majority of (72.38 %, N =173) of the respondents had failed one unit; 16.32% (39), two units; 8.37% (20), three units and 2.99% (7) four units respectively. The results showed that more than a half (52.24%) of the students who had failed some units during the January–April 2018 managed to pass all the units registered in the subsequent semester after exposure to mentorship. The percentage pass rate varied from programme to programme. Students registered for the BSc in Agribusiness and Trade programme recorded the highest percentage (70%) pass and those in Bachelor of Science in Mathematics recording the least improvement of 25%. It was concluded that properly organized and structured mentorship can drastically reduce the number of students who fail their examinations. It was recommended that universities through the schools and departments should institutionalize academic mentorship focusing mainly on low achieving students to minimize the number of students who fail each semester. This will improve progression and retention of students.
Keywords: mentorship; academic; low achievers; students